Gene–Environment Interplay in the Context of Romantic Relationships - Whisman, Mark A. (Curr Opin Psychol, 2016)
A growing body of research supports an important role for genetic factors on intimate, romantic relationships. In this article, we review research that has examined the interplay between genetic and environmental influences on romantic relationships and the associations between relationship outcomes and important individual differences related to relationships. We first elaborate on how behavioral genetic and molecular genetic methods can be used to understand the etiology of relationship outcomes. We then review empirical studies that have examined gene-environment correlations and gene-by-environment interactions in predicting romantic relationship outcomes (e.g., relationship formation, relationship quality and functioning, relationship dissolution) and their association with the physical health, mental health, and well-being of relationship partners.